Safety and Technique of Ferumoxytol Administration for MRI - Vasanawala, Shreyas S. (Magn Reson Med, 2016)
Ferumoxytol is an ultrasmall superparamagnetic iron oxide agent marketed for the treatment of anemia. There has been increasing interest in its properties as an MRI contrast agent as well as greater awareness of its adverse event profile. This mini-review summarizes the current state of knowledge of the risks of ferumoxytol and methods of administration.